2012
DOI: 10.6004/jnccn.2012.0063
|View full text |Cite
|
Sign up to set email alerts
|

Oral Chemotherapy Program Improves Adherence and Reduces Medication Wastage and Hospital Admissions

Abstract: Adherence, medication wastage, and reduction in hospital admissions were investigated in a retrospective test-control study design for patients enrolled in the oral chemotherapy cycle management program (CMP), a program that offers clinical support, dose monitoring, and early identification of side effects for patients on select oral chemotherapy. Patients who initiated oral chemotherapy with sorafenib, sunitinib, or erlotinib during June 2008 through December 2009 and who were enrolled in the CMP were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 10 publications
1
71
0
6
Order By: Relevance
“…In a total of 12 studies ( [44][45][46][47], treatment monitoring [48], pharmacy-based programs [42,49,50], counseling programs [51,52], prefilled pill boxes [53], and automated voice response systems [54]. Five of these studies were randomized trials, none of which demonstrated significant differences between the intervention and control groups with respect to their primary adherence outcomes [44,45,47,52,54].…”
Section: Interventions To Improve Adherence To Oral Antineoplastic Thmentioning
confidence: 99%
See 2 more Smart Citations
“…In a total of 12 studies ( [44][45][46][47], treatment monitoring [48], pharmacy-based programs [42,49,50], counseling programs [51,52], prefilled pill boxes [53], and automated voice response systems [54]. Five of these studies were randomized trials, none of which demonstrated significant differences between the intervention and control groups with respect to their primary adherence outcomes [44,45,47,52,54].…”
Section: Interventions To Improve Adherence To Oral Antineoplastic Thmentioning
confidence: 99%
“…One randomized, three-arm trial did show differences in adherence, favoring the intervention groups, when the investigators conducted a post hoc pooled analysis comparing both interventions to the control group [47]. The remaining investigations included two single-group studies (i.e., a feasibility pilot study [46] and a randomized crossover study [53]) and five investigations of nonrandomized observational cohorts with control groups [42,[48][49][50][51]. Of these investigations, only two nonrandomized cohort studies showed a significant benefit of their respective interventions for adherence to oral antineoplastic therapy relative to their control groups.…”
Section: Interventions To Improve Adherence To Oral Antineoplastic Thmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Furthermore, the substantial direct financial cost of oral agents can be increased by the cost of managing complications from adverse effects, drug-drug interactions, and poor adherence. Interventions to monitor adherence have improved outcomes and survival 6 as well as reduced cost 7 ; however, the feasibility of their widespread implementation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][51][52][53][54][55][56][57][58] Medication non-adherence can lead to adverse health outcomes, increased hospitalisations and health care costs. 3,12,18,55,59 The adverse impact of medication non-adherence grows as the burden of chronic diseases increases. 1 This section discusses the prevalence of non-adherence, and the clinical outcomes, hospitalisations and health care expenditure associated with medication non-adherence.…”
Section: Epidemiology Of Medication Non-adherencementioning
confidence: 99%